Evoluția relației dintre abordările conceptuale cu privire la dezvoltare și politicile de reducere a sărăciei - Panica, Daniela (Calitatea Vieții, 2023)
The main objectives of this paper are to describe the evolution of the concept of development and to evaluate the impact of those changes on poverty reduction methods. Both of these concepts have evolved following the same pattern and global trends, while having a distinct approach in different countries, in accordance with their location and development. By looking at these various definitions of development in chronological order, we can identify the effects of certain events and trends on how the relevant indicators were chosen to measure development, while also establishing their relation with poverty reduction policies and strategies.